TGF-β and mesenchymal stromal cells in regenerative medicine, autoimmunity and cancer. (October 2018) - de Araújo Farias, Virgínea; Carrillo-Gálvez, Ana Belén; Martín, Francisco; Anderson, Per
Abstract: Multipotent mesenchymal stromal cells (MSCs) represent a promising cell-based therapy in regenerative medicine and for the treatment of inflammatory/autoimmune diseases. Importantly, MSCs have emerged as an important contributor to the tumor stroma with both pro- and anti-tumorigenic effects. However, the successful translation of MSCs to the clinic and the prevention of their tumorigenic and metastatic effect require a greater understanding of factors controlling their proliferation, differentiation, migration and immunomodulation in vitro and in vivo . The transforming growth factor(TGF)-β1, 2 and 3 are involved in almost every aspect of MSC function. The aim of this review is to highlight the roles that TGF-β play in the biology and therapeutic applications of MSCs. We will discuss the how TGF-β modulate MSC function as well as the paracrine effects of MSC-derived TGF-β on other cell types in the context of tissue regeneration, immune responses and cancer. Finally, taking all these aspects into consideration we discuss how modulation of TGF-β signaling/production in MSCs could be of clinical interest.